Intraperitoneal drug delivery systems for peritoneal carcinomatosis: Bridging the gap between research and clinical implementation - Perelló-Trias, M. Teresa; Serrano-Muñoz, Antonio Jose; Rodríguez-Fernández, Ana; Segura-Sampedro, Juan José; Ramis, Joana Maria; Monjo, Marta (Journal of controlled release, 2024)
Several abdominal-located cancers develop metastasis within the peritoneum, what is called peritoneal carcinomatosis (PC), constituting a clinical challenge in their therapeutical management, often leading to poor prognoses. Current multidisciplinary strategies, including cytoreductive surgery (CRS), hyperthermic intraperitoneal chemotherapy (HIPEC), and pressurized intraperitoneal aerosol chemotherapy (PIPAC), demonstrate efficacy but have limitations. In response, alternative strategies are explored in the drug delivery field for intraperitoneal chemotherapy. Controlled drug delivery offers a promising avenue, maintaining localized drug concentrations for optimal PC management. Drug delivery systems (DDS), including hydrogels, implants, nanoparticles, and hybrid systems, show potential for sustained and region-specific drug release. The present review aims to offer an overview of the advances and current designs of DDS for PC chemotherapy administration, focusing on their composition, main characteristics, and principal experimental outcomes, highlighting the importance of biomaterial rationale design and in vitro/vivo models for their testing. Moreover, since clinical data for human subjects are scarce, we offer a critical discussion of the gap between bench and bedside in DDS translation, emphasizing the need for further research. [Display omitted] •Emphasis on the chemical and structural properties of drug delivery systems (DDS) for intraperitoneal chemotherapy (IPEC).•Analysis of key findings and clinical potential from testing DDS formulations on in vitro and in vivo cancer models.•Overview of the patent landscape and clinical trials, identifying development constraints to bridge the translational gap.